2-Methyl-3-[(4-methyl-phen-yl)sulfon-yl-oxy]-2-{[(4-methyl-phen-yl)sulfon-yloxy]meth-yl}propyl 4-methyl-benzene-sulfonate - Al-Mohammed, N.N.; Shakir, R.M.; Alias, Y.; Abdullah, Z.; Abd, H.S.N.; Tiekink, E.R. (International Union of Crystallography, 2011)
The title mol-ecule, C(26)H(30)O(9)S(3), adopts an extended conformation whereby two approximately parallel benzene rings [dihedral angle = 8.32 (10)°] are orientated in opposite directions along the pseudo-threefold axis through the central quaternary C atom, while a third ring occupies a position mid-way and face-on to these rings [dihedral angles = 82.28 (10) and 78.81 (7)°]. The crystal packing is dominated by C-H⋯O contacts and π-π inter-actions [ring centroid distance = 3.6902 (12) Å].